PENGARUH KOMPETENSI SUMBER DAYA MANUSIA,SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD),PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERN DAN PERAN INSPEKTORAT TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD KotaPekanbaru) - Tissa Nurul Husna; Muhammad Rasuli; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The sample in this study was determined by using purposive sampling method in total there are 32 SKPD in Pekanbaru city. The analytical method used in this research is multiple regression analysis using SPSS v16.The purpose of this study was to test the competence Effect of Human Resources, the Regional System of Financial Accounting, Information Technology Utilization, Internal Control System, and the role of the Inspectorate to the quality of financial statements. Respondents in this study is the structural officials involved in drafting the budget. The results showed that: 1) Effect of Human Resources positively affect the quality of financial reports with significant value 0,000 <0,05.2), Regional Financial Accounting System significantly influence the quality of financial statements with significant value 0,000 <0.05.3) the utilization of the positive impact of Information Technology and significant impact on the quality of financial statements with significant value 0,000 <0.05.4) Internal Control System a significant effect on the quality of financial statements with significant value 0.001 <0.05.5) the role of the Inspectorate significant positive effect on the quality of financial statements with significant value 0,019 <0,05.Keyword : competence, accounting sistem, information technology, internal control,inspectorate, quality